Optimum Design of Electric Scooter for Longer Operating Time - W.A. Akpan; I.I. Nyaudo; O. W. Obot (Engineering And Technology Journal, 2024)
Electric scoter has come to stay as a mobility device with various uses in sporting, transportation and leisure. Electric vehicles are proven to be one of the promising solutions to the global environmental problem caused by emission of greenhouse gases from fossil fuels, thus there is need to produce new designs to meet immediate demand. This research work was focused on computer aided design of electric scooter to enhance longer operating time for the ‘scot-man’ The electric scooter produced was successfully tested and satisfactory performance obtained.